Development of Learning Media Game Computer Assembly (GAPEKO) Android Based on Computer Assembly Subjects for Students TKJ SMK Negeri 1 Sukoharjo - Mutri Widiasih; Yudianto Sujana; A G Thamrin (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
Research and development is aimed to (1) make the game computer assembly (GAPEKO) android based on computer assembly subjects for students TKJ SMK Negeri 1 Sukoharjo to support the material practice of computer assembly (2) to investigate the feasibility of learning media game computer assembly (GAPEKO) android based on computer assembly subjects for students TKJ SMK Negeri 1 Sukoharjo. GAPEKO learning media is developed by Adobe Flash Professional CS6 and published as an .apk file to be installed and used on android phone. Research and development is carried out with a model of the development of DDD-E (Decide, Design, Develop, Evaluate). The results of the feasibility study and measurement of media expert obtained a percentage of 78.23% is categorized as very feasible, material expert obtained a percentage of 91.67% is categorized as very feasible, and the test results obtained by a percentage of 81.35% users categorized as very feasible. Based on the measurement results feasibility it can be concluded that the learning media game computer assembly (GAPEKO) android based on computer assembly subjects for students TKJ SMK Negeri 1 Sukoharjo included in the category of very feasible to use, both from the aspect of media, materials, and users.